2016
DOI: 10.1097/dad.0000000000000454
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Analysis of 226 Patients With Rosacea According to Rosacea Subtype and Severity

Abstract: The intensity of inflammatory reactions, especially perifollicular infiltration, was higher in PPR patients than in ETR patients. Rosacea has a spectrum of histopathological features that are related to clinical progression between rosacea subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 22 publications
1
26
0
3
Order By: Relevance
“…There is no specific histological feature associated with either erythematotelangiectatic or papulopustular clinical forms . Perivascular and perifollicular lymphohistiocytic infiltration were common dermal findings and occurred irrespective of the morphology of the skin lesions, but the intensity of dermal inflammatory infiltration was higher in papulopustular lesions than in erythematotelangiectatic lesions . These histopathological findings suggest that erythematotelangiectatic eruption could be considered the initial and essential lesion of rosacea, and may progress to other subtypes such as papulopustular eruptions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…There is no specific histological feature associated with either erythematotelangiectatic or papulopustular clinical forms . Perivascular and perifollicular lymphohistiocytic infiltration were common dermal findings and occurred irrespective of the morphology of the skin lesions, but the intensity of dermal inflammatory infiltration was higher in papulopustular lesions than in erythematotelangiectatic lesions . These histopathological findings suggest that erythematotelangiectatic eruption could be considered the initial and essential lesion of rosacea, and may progress to other subtypes such as papulopustular eruptions.…”
Section: Discussionmentioning
confidence: 95%
“…provided evidence that patients with ETR may progress to PPR and PHY. Histopathological results supporting progression between subtypes of rosacea have been reported . There is no specific histological feature associated with either erythematotelangiectatic or papulopustular clinical forms .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Though it is well known that vascular ectasia and perivascular and perifollicular inflammation are common histopathologic findings irrespective of rosacea subtypes, 3,4 there is no study focusing on sebaceous gland changes in rosacea. In this study, we observed that in most of the cases of rosacea, the inflammatory cells infiltrate around the sebaceous glands as well as exhibiting perifollicular and perivascular infiltration.…”
Section: Sebaceous Glands Participate In the Inflammation Of Rosaceamentioning
confidence: 99%
“…The presence of anti-skin autoantibodies in patients suffering from congenital EB has been reported. [2][3][4][5] However, direct immunofluorescence (DIF) and indirect IF (IIF) are usually negative suggesting a not-pathogenic role of these autoantibodies. The meaning of the anti-skin humoral response in EB patients remains to be elucidated.…”
Section: Development Of Bullous Pemphigoid In Junctional Epidermolysimentioning
confidence: 99%